Effect of dentin conditioners on the microtensile bond strength of a conventional and a self-etching primer adhesive system - Jacques, Paula (2005)
The effect of different dentin conditioners on the microtensile bond strength of a self-etching primer and a total-etch adhesive system was investigated. Clearfil SE primer for 20s, 37% phosphoric acid for 15s, or 0.5 M ethylenediamine-tetraacetic acid (EDTA) for 30s are used as conditioners for the surface treatment of the flat dentin surfaces created on the extracted human third molar. it was found that the highest bond strength mean was for the combination SE primer/single bond, followed by the EDTA/clearfil SE bond and phosphoric acid/single bond. It was observed that smear layer removal with 0.5 M EDTA before using self-etching primer produced higher bond strengths.